(untitled) (Research, Society and Development, 2023)
Introduction: Diabetes mellitus is a public health problem, with 537 million people aged 20-79 years affected. The complexity of the pathology, the difficulty of management, and its economic impact make it important to search for low-cost interventions. Nutritional educational interventions are actions that improve adherence to non-pharmacological treatment, which can improve clinical outcomes and reduce associated costs. Objective: This study aimed to evaluate the main impacts of nutritional educational interventions on improving the quality of life of patients with type 2 diabetes mellitus (DM2). Methodology: A systematic review was carried out based on a survey of studies in the National Library of Medicine (PubMed), Web of Science, Scopus and Virtual Health Library (BVS) databases, from 2017 to 2022. Six studies fulfilled the criteria. Inclusion criteria. Results: A significant effect on quality of life was observed in interventions that carried out nutrition education, individually, with support and regular checks, in those carried out with follow-up focus groups, and in those combined with physical exercises. The findings seem to indicate a relevant impact on health components in general, such as functional capacity, physical and mental health, as well as improvement in knowledge, weight loss, decrease in waist/hip circumference and glycated hemoglobin (HbA1c). Conclusion: The study showed that nutritional interventions can improve the quality of life of DM2 patients, with clinical, cognitive and laboratory impacts, although further studies are recommended.